"MusiMath" - a music-based intervention program for learning patterns and symmetry. Issue 2 (3rd April 2022) - Azaryahu, Libby; Adi-Japha, Esther
Abstract: Researchers have recently queried whether musical activities that express mathematical concepts enhance young students' math skills. The use of abstract notations for math learning is also debated. The current study examined the effect of a music intervention program on pattern and symmetry knowledge. Simple graphical notation-writing was used for clarifying the abstractness of the music form and its relation to mathematical concepts. Four third-grade classes attended ten lessons on patterns and symmetry: two music classes ( n   = 48), and two comparison classes ( n  = 48). The students in the music classes were taught to write symbolic representations of musical properties and to recognize patterns and symmetry via the symbols they wrote. Pre- to post-intervention analyses indicated that the integrated music/math intervention groups had higher pre-to-post gains on math tests scores that were retained 6-months post-intervention. Students in the music groups also showed effective learning of notation-writing and transfer of note writing knowledge to a different musical piece. The music-math intervention enabled students to acquire knowledge about patterns and symmetry through repeated experiences, particularly through music-related notation-writing, suggesting that multiple representations facilitated deeper understanding and learning outcomes.